1994
DOI: 10.3354/meps109059
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of the life cycle and dispersal pattern of the tropical invader scyphomedusan Rho-pilema nomadica is temperature dependent

Abstract: During the last decade, an Indo-Pacific scyphomedusa, Rhopilema nomadica, penetrated the eastern Mediterranean. Annual blooms of the medusa near the Israeli coast were observed during the summer months of the years 1989 to 1992. R. nomadjca migrated northward from the Israeli coast towards Lebanon and Syria and has not been found elsewhere in the Mediterranean. Temperature dependence of the metamorphosis of R. nornadica polyps into strobila was studied in the laboratory. Rapid strobilation occurred between 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 8 publications
2
44
1
Order By: Relevance
“…More likely is that sharp thermal variations within such estuarine / coastal environments may themselves trigger multiple releases of ephyrae, as shown for the giant jellyfish Nemopilema nomurai (>2 m bell diameter) under laboratory conditions (Kawahara et al, 2006). Indeed, it is well established that thermal elevation is one of the triggers inducing strobilation in rhizostome jellyfish (Kawahara et al, 2006), as previously reported for Cephea cephea (Sugiura, 1966), Rhopilema esculentum (Chen and Ding, 1983) and Rhopilema nomadica (Lotan et al, 1994). As the scyphistoma of rhizostome jellyfish (Nemopilema nomurai) are capable of asexual reproduction for >1.5 years (Kawahara et al, 2006) the notion of protracted and repeated ephyrae release in the Irish Sea is certainly possible, although bespoke investigations of this claim are clearly required.…”
Section: Discussionmentioning
confidence: 60%
“…More likely is that sharp thermal variations within such estuarine / coastal environments may themselves trigger multiple releases of ephyrae, as shown for the giant jellyfish Nemopilema nomurai (>2 m bell diameter) under laboratory conditions (Kawahara et al, 2006). Indeed, it is well established that thermal elevation is one of the triggers inducing strobilation in rhizostome jellyfish (Kawahara et al, 2006), as previously reported for Cephea cephea (Sugiura, 1966), Rhopilema esculentum (Chen and Ding, 1983) and Rhopilema nomadica (Lotan et al, 1994). As the scyphistoma of rhizostome jellyfish (Nemopilema nomurai) are capable of asexual reproduction for >1.5 years (Kawahara et al, 2006) the notion of protracted and repeated ephyrae release in the Irish Sea is certainly possible, although bespoke investigations of this claim are clearly required.…”
Section: Discussionmentioning
confidence: 60%
“…Survival of C. tuberculata polyps from the Mar Menor was 100% at 16°C, but all polyps at lower temperatures (2, 4, and 9°C) died in B32 days (Prieto et al, 2010). Polyps of Rhopilema nomadica Galil, Spanier & Ferguson, 1990 from Mediterranean waters off Israel (16-28°C) survived at temperatures between 11 and 26°C, but did not feed below 13°C (Lotan et al, 1994). Similar results were reported for Rhopilema esculentum Kishinouye 1891 polyps (Chen et al, 1985).…”
Section: Survivalmentioning
confidence: 98%
“…Differences in strobilation of A. aurita polyps from Germany at 14-15°C (100% of polyps from the Baltic Sea, Kiel strobilated vs. 5-6.5% from the North Sea, Helgoland) and in the numbers ephyrae Lotan et al (1994) 24-26 ND *3…”
Section: Strobilationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the opening of the Suez Canal in 1869, more than 300 Red Sea species of algae, invertebrates and fish have entered the Mediterranean through the canal (Safriel and Ritte 1986;Spanier and Galil 1991;Barash and Denin 1992;Lotan et al 1994;Golani 1998;Galil 2000). For example, the invasive jellyfish Rhopilema nomadica appears in mass swarms along the Mediterranean coasts of Israel every summer, causing severe damage to coastal fishing, tourism and coastal installations (Spanier and Galil 1991).…”
Section: Introductionmentioning
confidence: 99%